2007
DOI: 10.1021/ja072281h
|View full text |Cite
|
Sign up to set email alerts
|

Surface Structures of Rutile TiO2 (011)

Abstract: Surface structures of rutile TiO(2) (011) are determined by a combination of noncontact atomic force microscopy (NC-AFM), scanning tunneling microscopy (STM), and density functional calculations. The surface exhibits rowlike (n x 1) structures running along the [01] direction. Microfaceting missing-row structural models can explain the experimental results very well. Calculated images for NC-AFM and STM are in good agreement with the experimental results. A decrease of the density of dangling bonds stabilizes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
81
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(89 citation statements)
references
References 39 publications
7
81
1
Order By: Relevance
“…The validity of the titanyl model was recently questioned by Kubo et al [18]. These authors reported that the titanyl structure is highly unstable and unlikely to occur (details of calculations were not provided), and, as an alternative, proposed a 'microfaceting' model where the removal of a pair of apex Ti 5c -O 2c gives rise to a 2 Â 1 surface periodicity.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The validity of the titanyl model was recently questioned by Kubo et al [18]. These authors reported that the titanyl structure is highly unstable and unlikely to occur (details of calculations were not provided), and, as an alternative, proposed a 'microfaceting' model where the removal of a pair of apex Ti 5c -O 2c gives rise to a 2 Â 1 surface periodicity.…”
Section: Resultsmentioning
confidence: 99%
“…In one report, the photo-induced oxidative and reductive half-reactions were observed to take place predominantly on the (0 1 1) and (1 1 0) surfaces of well-faceted TiO 2 microcrystals, respectively [11]. The need to understand such phenomena and the dearth of information on rutile (0 1 1) as compared to other TiO 2 surfaces has recently stimulated several surface science studies on single crystal TiO 2 (0 1 1) [13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…First-principles calculations (T = 0 K) of the energetics and structure of stoichiometric TiO 2 surfaces were communicated by Ramamoorthy et al [59] and revealed that the (011) surface should be more corrugated than the (110) surface and dominated by five-fold coordinated Ti atoms. A combined (non-contact) atomic-force microscopy (AFM) and STM study including DFT calculations by Kubo et al [78] led to a similar interpretation of the (2 1) reconstructed (011) surface with some minor differences. The authors suggested a micro-faceting missing-row reconstruction.…”
Section: (011)-oriented Rutile Thin Filmsmentioning
confidence: 93%
“…A scanning tunneling microscopy (STM) and density functional theory (DFT) investigation of TiO 2 (0 1 1)(2 Â 1) has suggested a surface terminated by titanyl (Ti@O) groups, possibly a cause of the enhanced photo-catalytic activity [4]. Another similar study suggested a microfaceting missing-row model [5]. More recent surface X-ray diffraction (SXRD) studies, however, have yielded data inconsistent with these two models and instead favored qualitively similar structures terminated by zigzag rows of twofold coordinated oxygen atoms asymmetrically bonded to fivefold titanium atoms [6,7].…”
Section: Introductionmentioning
confidence: 99%